GAYA BAHASA NOVEL CINTA SUCI ZAHRANA KARYA HABIBURRAHMAN EL SHIRAZY: KAJIAN STILISTIKA - Sasmi, Sinta Wira; Nurizzati, Nurizzati; Nasution, Muhammad Ismail (Jurnal Bahasa dan Sastra, 2014)
The purpose of this article is to describe (a) the structure of the novel Cinta Suci Zahrana by Habiburrahman El Shirazy, (b) the type of style that is used in the novel Cinta Suci Zahrana by Habiburrahman El Shirazy, (c) the functions contained in the language style of the novel Cinta Suci Zahrana by Habiburrahman El Shirazy. The data of this research is the novel style in novel Cinta Suci Zahrana by Habiburrahman El Shirazy. The technique of analyzing data using techniques detailed description. The study findings in this novel as follows: 8 units personification, similes style of 4 pieces, style 3 pieces allegory, metaphor style as much as 9 pieces, style satire as much 2 pieces, style parable as much 2 pieces, style cynicism as much as 2 pieces, stylistic allusions 3 pieces, the eponymous style as much as 1 piece, style as much as 1 piece of irony, sarcasm style 5 pieces, and ntonomasia style as much as 2 pieces and a paronomasia 1 piece. functional style of language in the novel Sacred Love Habiburrahman El Shirazy Zahrana work is to give a wonderful effect on the language used in the story. Functions of language style in this study includes beautifying function, define the function, the function of satire, functional equations and functional comparison.